2019
DOI: 10.1002/ccd.28634
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical and procedural outcomes in large series of 34‐mm self‐expanding transcatheter aortic valve replacement

Abstract: Objectives: We aimed to evaluate early clinical and procedural outcomes with the 34-mm Evolut R transcatheter aortic valve replacement (TAVR) prosthesis. Background: The 34-mm Evolut R (Medtronic, Minneapolis, MN) self-expanding TAVR prosthesis was designed to treat patients with larger annuli. Methods: Clinical, demographic, procedural, and echocardiographic data on consecutive patients who underwent TAVR with a 34-mm Evolut R prosthesis at our institution were collected and analyzed. Results: One hundred nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…Although we found the rate of moderate-severe PVL similar to previous studies, we found a lower rate of mild PVL. 6 , 7 , 10 We also observed that PVL improved over time in patients treated with self-expandable valves, as previously reported. 7 In a study published in 2021, 60° aortic angulation was found to be a predictor of ≥moderate PVL for the Evolut-R 34 mm valve.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although we found the rate of moderate-severe PVL similar to previous studies, we found a lower rate of mild PVL. 6 , 7 , 10 We also observed that PVL improved over time in patients treated with self-expandable valves, as previously reported. 7 In a study published in 2021, 60° aortic angulation was found to be a predictor of ≥moderate PVL for the Evolut-R 34 mm valve.…”
Section: Discussionsupporting
confidence: 88%
“… 6 , 7 , 10 We also observed that PVL improved over time in patients treated with self-expandable valves, as previously reported. 7 In a study published in 2021, 60° aortic angulation was found to be a predictor of ≥moderate PVL for the Evolut-R 34 mm valve. 10 However, in our study, we aimed to determine the predictors of ≥mild PVL in both Evolut-R 34 mm and Evolut-R 23/26/29 mm valves.…”
Section: Discussionsupporting
confidence: 88%